Finding concurrency bugs with context-aware communication graphs - Lucia, Brandon; Ceze, Luis (2009 42nd Annual IEEE/ACM International Symposium on Microarchitecture (MICRO), 2009)
Incorrect thread synchronization often leads to concurrency bugs that manifest nondeterministically and are difficult to detect and fix. Past work on detecting concurrency bugs has addressed the general problem in an ad-hoc fashion, focusing mostly on data races and atomicity violations. Using graphs to represent a multithreaded program execution is very natural, nodes represent static instructions and edges represent communication via shared memory. In this paper we make the fundamental observation that such basic context-oblivious graphs do not encode enough information to enable accurate bug detection. We propose context-aware communication graphs, a new kind of communication graph that encodes global ordering information by embedding communication contexts. We then build Bugaboo, a simple and generic framework that accurately detects complex concurrency bugs. Our framework collects communication graphs from multiple executions and uses invariant-based techniques to detect anomalies in the graphs. We built two versions of Bugaboo: BB-SW, which is fully implemented in software but suffers from significant slowdowns; and BB-HW, which relies on custom architecture support but has negligible performance degradation. BB-HW requires modest extensions to a commodity multicore processor and can be used in deployment settings. We evaluate both versions using applications such as MySQL, Apache, PARSEC, and several others. Our results show that Bugaboo identifies a wide variety of concurrency bugs, including challenging multivariable bugs, with few (often zero) unnecessary code inspections.